Mechanics of materials - Beer, Ferdinand P. (Ferdinand Pierre), 1915-2003; Johnston, E. Russell (Elwood Russell), 1925-2010; DeWolf, John T.; Mazurek, David F. (David Francis) (2015)
Beer and Johnston's Mechanics of Materials is the uncontested leader for the teaching of solid mechanics. Used by thousands of students around the globe since publication, Mechanics of Materials, provides a precise presentation of the subject illustrated with numerous engineering examples that students both understand and relate to theory and application. The tried and true methodology for presenting material gives your student the best opportunity to succeed in this course. From the detailed examples, to the homework problems, to the carefully developed solutions manual, you and your students can be confident the material is clearly explained and accurately represented. McGraw-Hill is proud to offer Connect with the seventh edition of Beer and Johnston's Mechanics of Materials.